2018
DOI: 10.1016/j.jaci.2017.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Sputum transcriptomics reveal upregulation of IL-1 receptor family members in patients with severe asthma

Abstract: Background: Sputum analysis in asthma is used to define airway inflammatory processes and may guide therapy. Objective: To determine differential gene and protein expression in sputum samples from patients with severe asthma (SA) compared to mildmoderate non-smoking asthmatics (MMA). Methods: Induced sputum was obtained from non-smoking SA (SAn), smokers/ex-smokers with SA (SAsm), MMA and healthy non-smoking controls. Differential cell counts, microarray analysis of cell pellets and SOMAscan analysis of sputum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 34 publications
10
136
1
Order By: Relevance
“…As indicated in the introduction, other recent studies in severe asthma have reported mainly transcriptomic gene expression data from various cell sources, including sputum, epithelial brush and biopsy, in addition to more limited information for protein analysis. Proteins identified by Somascan in sputum supernatants of U‐BIOPRED subjects presented only mild/moderate asthma, or severe asthma data (either smoking or not) compared to healthy controls subjects, without comparison between mild/moderate and severe asthma groups . They noted upregulation of IL‐1 receptor family members by gene expression in those with severe asthma not only compared to healthy controls but also to the mild/moderate asthma group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated in the introduction, other recent studies in severe asthma have reported mainly transcriptomic gene expression data from various cell sources, including sputum, epithelial brush and biopsy, in addition to more limited information for protein analysis. Proteins identified by Somascan in sputum supernatants of U‐BIOPRED subjects presented only mild/moderate asthma, or severe asthma data (either smoking or not) compared to healthy controls subjects, without comparison between mild/moderate and severe asthma groups . They noted upregulation of IL‐1 receptor family members by gene expression in those with severe asthma not only compared to healthy controls but also to the mild/moderate asthma group.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this approach avoids reliance on measures of mRNA which lack linear association with actual protein synthesized . Although several recent reports have examined gene expression patterns in sputum and bronchial epithelial samples from subjects with severe asthma, these have included more limited information on corresponding protein analyses . One report from U‐BIOPRED, examining protein differences between 4 clinically identified cluster groups, found 9 differentially abundant sputum proteins in more severe clusters compared to moderate, well‐controlled asthma with normal FEV1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-type 2 asthma, observed more often in obesity-related asthma, neutrophilic asthma, and paucigranulocytic asthma (Kuo et al, 2017;Cosío et al, 2017;Ray and Kolls, 2017), is usually connected with poor responsiveness to steroids and more severe phenotypes, even in childhood (Ramratnam et al, 2017). Nontype 2 inflammation is characterized by infiltration of Th1 and Th17 cells and neutrophils, the presence of type I interferons, NLRP3 inflammasome activation, and an IL-1b and IL-17 signature (Rossios et al, 2018;Kim et al, 2017;Tan et al, 2019). The effect of microbiota dysbiosis on asthma heterogeneity seems intuitive, but, until recently (Taylor et al, 2018;Boutin et al, 2017), lung and gut microbiome composition have not been addressed in (Turnbaugh et al, 2007), lungs were not sampled, partially due to the existing dogma at the time that lungs are sterile.…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
“…It has also been reported that the inhibition of NLRP3 prevents neutrophilia and decreases airway hyper-responsiveness. 34 CPA3 is a metalloexopeptidase specifically expressed in a particular subtype of mast cells in combination with tryptase. 35 Expression of CPA3 has been associated with TH2-high asthma in sputum and epithelial brushings of steroid naïve asthma.…”
Section: Discussionmentioning
confidence: 99%